2018
DOI: 10.3389/fnagi.2018.00304
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Precuneus/Posterior Cingulate Cortex Is Significant for the Development of Alzheimer’s Disease: A PET (THK5351, PiB) and Resting fMRI Study

Abstract: Background: Imaging studies in Alzheimer’s disease (AD) have yet to answer the underlying questions concerning the relationship among tau retention, neuroinflammation, network disruption and cognitive decline. We compared the spatial retention patterns of 18F-THK5351 and resting state network (RSN) disruption in patients with early AD and healthy controls.Methods: We enrolled 23 11C-Pittsburgh compound B (PiB)-positive patients with early AD and 24 11C-PiB-negative participants as healthy controls. All partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 74 publications
4
72
0
2
Order By: Relevance
“…Specifically, ET patients are characterized by lower small-worldness values of the network-less clustered functionality of the brain-together with altered connectivity patterns in specific systems. False discovery rate correction for multiple comparisons was applied to the significance level for the correlation contrasts between the significant ROIs T A B L E 4 Regional graph topological differences and its relationship with the pathogenesis of ET (Yokoi et al, 2018) Older-onset ET is associated not only with higher odds of prevalent Alzheimer's disease (Benito-León et al, 2006a), but also with an increased risk of Alzheimer's disease Frontal operculum This is a key node in a network for exerting control over cognitive processes (Higo, Mars, Boorman, Buch, & Rushworth, 2011) Cognitive deficits have been described in ET (Benito-León et al, 2006b). At the regional level, we found the existence of multiple connectivity differences between ET patients and healthy controls in motor and extramotor related areas.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ET patients are characterized by lower small-worldness values of the network-less clustered functionality of the brain-together with altered connectivity patterns in specific systems. False discovery rate correction for multiple comparisons was applied to the significance level for the correlation contrasts between the significant ROIs T A B L E 4 Regional graph topological differences and its relationship with the pathogenesis of ET (Yokoi et al, 2018) Older-onset ET is associated not only with higher odds of prevalent Alzheimer's disease (Benito-León et al, 2006a), but also with an increased risk of Alzheimer's disease Frontal operculum This is a key node in a network for exerting control over cognitive processes (Higo, Mars, Boorman, Buch, & Rushworth, 2011) Cognitive deficits have been described in ET (Benito-León et al, 2006b). At the regional level, we found the existence of multiple connectivity differences between ET patients and healthy controls in motor and extramotor related areas.…”
Section: Discussionmentioning
confidence: 99%
“…The cingulate area, especially PCC, is one of the earliest regions to exhibit hypometabolism (Mosconi, 2005). Studies on differential susceptibility using PET reported hypometabolism in PCC, but not in the ACC region of early AD (Minoshima et al, 1997;Yokoi et al, 2018) and also in MCI patients (Tomadesso et al, 2015). However, few studies have reported a significant hypometabolism in both the ACC and PCC regions in AD (Bailly et al, 2015;Chetelat et al, 2008;Hauser et al, 2013) as well as in apolipoprotein E (APOE) carriers, when compared to noncarriers (Langbaum et al, 2010).…”
mentioning
confidence: 99%
“…Studies have shown that these same parietal and limbic areas—which are associated with the executive attention and multi‐tasking networks—are selectively affected in mild AD and overlap with regional patterns of brain atrophy, glucose hypometabolism, and hypoperfusion . Furthermore, brain regions showing early amyloid and tau protein deposits overlap with posterior parts of the cognitive control and default mode networks . We interpret these findings as suggesting at least in part, a common pathological mechanism in AD that contributes to both bone loss and decreased functional connectivity in the left PCC.…”
Section: Discussionmentioning
confidence: 60%